Jacobi operators and orthonormal matrix-valued polynomials. II - Hatamleh, R.; Zolotarev, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We use a system of operator-valued orthogonal polynomials to construct analogs of L. de Branges spaces and establish their relationship with the theory of nonself-adjoint operators.